The role and importance of teaching aids in the teaching and learning process, mathematics as a model - Mohamed SAKHRI (Social Sciences Journal, 1970)
The topic of teaching methods preoccupied most of the active in thepsychological and educational field's interest due to its originality and it'seducational authenticity whereas many International Educational Systems head toboth techniques and technology with the objective of linking the best learned with thenewest educational methods to get out with a new high educational directrices thatfit with the blast of knowledge that created a competition to make learning andteaching process exceptional .This paper was meant to highlight the important roles of the educationalmethods in learning as a core issue that inspires its research from the importance ofeducational act